The Practice of Corporate Social Responsibility in Halal-Certified Businesses in Bangladesh - Hossain, Mohammad Faruk (2023)
Corporate Social Responsibility (CSR) refers to corporate action that helps achieving a sustainable society through positive contributions. In Islam, the idea of CSR has been an integral part of business for nearly fourteen centuries. Unfortunately, the concept of CSR per Sharia has not been practised even in Sharia-based businesses due to the lack of practical discussion and concentration. This study, therefore, reconnoitres CSR per Sharia in Halal-certified businesses in Bangladesh to promote responsible and ethical business practices. The primary focus of this research is to analyse the law, policies, and guidelines relating to CSR that is applicable in Halal-certified businesses, also to assess their strengths and weaknesses, which may affect the implementation of CSR in Halal-certified businesses in Bangladesh. The study also analyses the practices of CSR in Halal-certified businesses so as to understand whether it fulfils the concept of CSR. This study proposes improvements to the current CSR practices in Halal-certified businesses in Bangladesh by considering Sharia principles, Sharia-based universal CSR reporting guidelines, and CSR practices in Malaysia. To achieve the described objectives, this study embarked on qualitative research using library research and interviews. This study concludes that the current practice of CSR in Halal-certified businesses in Bangladesh is weak. The existing laws are ineffective and cannot ensure CSR in Halal-certified businesses. Consequently, the researcher recommends Bangladesh to improve the laws, set up CSR surveillance, and expand initiatives to increase public awareness regarding the concept of CSR per Sharia. The findings of this study can be the basis for setting up an effective mechanism of CSR or becoming an entry point to initiate legal drafting on CSR in Halal-certified businesses.